Efektivitas latihan pernapasan dalam mengurangi kecemasan kompetitif pada atlet sepatu roda - Khen, Cinta Angelly; Jannah, Miftakhul; Himawanto, Wasis (Universitas Nusantara PGRI Kediri, 2025)
Competitive anxiety can impair an athlete's performance, particularly in high-pressure events such as the National Student Sports Week (POMNAS). Research on breathing-based anxiety regulation for roller skaters remains limited, despite the sport's high psychophysiological demands. This study examined changes in Cognitive Anxiety, Somatic Anxiety, and Self-Confidence before and after a breathing exercise intervention among roller skating athletes. A one-group pre-test post-test design was used due to participant limitations and competitive conditions that did not allow group division. Seven athletes (4 males, 3 females), aged 17–21 years, from the East Java contingent were selected using purposive sampling. Competitive anxiety was measured using the CSAI-2R (α = 0.89), covering Cognitive Anxiety, Somatic Anxiety, and Self-Confidence. The intervention consisted of a diaphragmatic 4-4-4 breathing routine performed for 10–15 minutes. Data were analyzed using a paired samples t-test (α = 0.05). The results showed significant reductions in Cognitive Anxiety (t = 2.97; p = 0.025; d = 1.12; mean decrease = 1.43 points / 13.0%) and Somatic Anxiety (t = 3.04; p = 0.023; d = 1.15; mean decrease = 2.72 points / 19.0%), indicating large effect sizes. In contrast, Self-Confidence showed no change (t = 0.00; p = 1.00; d = 0.00), confirming that anxiety and confidence function as independent constructs. These findings show that brief breathing exercises effectively reduce short-term anxiety, although additional psychological methods are needed to improve confidence. The study provides practical guidance for integrating controlled breathing routines into pre-competition preparation.